Anomalous Protein-Protein Interactions in Multivalent Salt Solution - Pasquier, Coralie; Vazdar, Mario; Forsman, Jan; Jungwirth, Pavel; Lund, Mikael (The journal of physical chemistry. B, 2017)
The stability of aqueous protein solutions is strongly affected by multivalent ions, which induce ion-ion correlations beyond the scope of classical mean-field theory. Using all-atom molecular dynamics (MD) and coarse grained Monte Carlo (MC) simulations, we investigate the interaction between a pair of protein molecules in 3:1 electrolyte solution. In agreement with available experimental findings of "reentrant protein condensation", we observe an anomalous trend in the protein-protein potential of mean force with increasing electrolyte concentration in the order: (i) double-layer repulsion, (ii) ion-ion correlation attraction, (iii) overcharge repulsion, and in excess of 1:1 salt, (iv) non Coulombic attraction. To efficiently sample configurational space we explore hybrid continuum solvent models, applicable to many-protein systems, where weakly coupled ions are treated implicitly, while strongly coupled ones are treated explicitly. Good agreement is found with the primitive model of electrolytes, as well as with atomic models of protein and solvent.
Keywords: vazba proteinů; Molecular Dynamics Simulation; Yttrium; Solutions; simulace molekulární dynamiky; Humans; metoda Monte Carlo; lidský sérový albumin; roztoky; Serum Albumin, Human; lidé; Salts; soli; ytrium; Protein Stability; Protein Binding; stabilita proteinů; Monte Carlo Method